2004
DOI: 10.1128/jcm.42.6.2766-2768.2004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Enterohepatic Helicobacter Species in Patients Suffering from Inflammatory Bowel Disease

Abstract: Using a group-specific PCR assay, we investigated the presence of enterohepatic Helicobacter species in gut specimens from patients with inflammatory bowel disease. Enterohepatic Helicobacter species were detected in 12% (3 of 25) of the patients with Crohn's disease, in 17% (3 of 18) of the ulcerative colitis samples, and in 4% (1 of 23) of the controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 23 publications
0
74
2
1
Order By: Relevance
“…Thus, in the earliest studies on the subject, it was not possible to detect DNA of any EHH in colonic mucosa samples (80). However, more recent studies have found a statistically significant relation between EHH and IBD (83,84). Laharie et al (81) analyzed the presence of DNA of these bacteria by PCR in a total of 44 samples obtained by colonoscopy in patients with Crohn´s disease and healthy controls.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in the earliest studies on the subject, it was not possible to detect DNA of any EHH in colonic mucosa samples (80). However, more recent studies have found a statistically significant relation between EHH and IBD (83,84). Laharie et al (81) analyzed the presence of DNA of these bacteria by PCR in a total of 44 samples obtained by colonoscopy in patients with Crohn´s disease and healthy controls.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Thus, H. pullorum, H cinaedi, H. canis, H. bilis and H. muridarum have been described as responsible for this type of condition in poultry and domestic animals (4). In humans, these microorganisms have been detected by PCR in stools of patients with acute gastroenteritis (8,(71)(72)(73)(74)(75) and have been related with cases of Meckel´s diverticulum (76)(77)(78), acute appendicitis (79) and with inflammatory bowel disease (80)(81)(82)(83)(84)(85).…”
Section: Ehh and Intestinal Diseasementioning
confidence: 99%
“…Currently, the data on whether the presence of Helicobacter species is increased in patients with IBD are inconclusive. While some studies have found an increased prevalence rate (3,10,12,14,18,21), other studies have found otherwise (1, 2, 5, 7, 13). Discrepancies among studies may be explained by geographical and genetic differences among countries and populations and/or differences in disease stage, the length of time since initial diagnosis, and previous antibiotic or other treatments received.…”
mentioning
confidence: 90%
“…In our study of 72 patients (35 with IBD), Helicobacter species were detected in only 6 subjects (3 IBD, 3 controls) 82 . In another study, Helicobacter species were not detected in any of the 50 patients or 25 controls 83 , yet in a third study, 6 Helicobacter species were detected in 43 patients and only once in 23 controls 84 . A study using culture, detected only H. pylori on the colonic mucosa but there was no correlation with disease 85 .…”
Section: Non-pylori Helicobacter Speciesmentioning
confidence: 99%